Postawa Michała Walewskiego, marszałka konfederacji barskiej ziemi krakowskiej, wobec zabiegów polityczno-wojskowych wokół fortecy tynieckiej (maj-czerwiec 1772 r.) = The attitude of Michał WalewskiI, marshal of the Bar Confederation in the Kraków Voivodeship, to the political and military manoeuvring over the fortress of Tyniec (May-June 1772) - Dziewulski, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Bar Confederation, which began in 1768 and was defeated in 1772, was followed by the partitioning of Poland. One of the last fortresses in the Confederate hands was the Benedictine monastery of Tyniec, 10 km from Cracow, besieged by the Russian army of General A. Suvorov. Also interested in the seizure of the fortress were the Austrian troops under R. d?Alton, following the Habsburg claim to the lands on the right bank of the Vistula. In view of the fact that the supreme authority of the Confederation, the Generality, had fled abroad, Michał Walewski entered into negotiations in order to pass control of the fortress to the Polish King, and (when it proved impossible) to the Russian forces.
Keywords: Walewski, Michał (1735-1806); Benedyktyńskie Opactwo Świętych Apostołów Piotra i Pawła (Tyniec) - historia; Kraków (Polska) -- Opactwo Benedyktynów w Tyńcu; 18 w.